Advanced maternal age and risk perception: A qualitative study - Bayrampour Hamideh; Heaman Maureen; Duncan Karen A; Tough Suzanne (BMC, 2012)
Abstract Background Advanced maternal age (AMA) is associated with several adverse pregnancy outcomes, hence these pregnancies are considered to be "high risk." A review of the empirical literature suggests that it is not clear how women of AMA evaluate their pregnancy risk. This study aimed to address this gap by exploring the risk perception of pregnant women of AMA. Methods A qualitative descriptive study was undertaken to obtain a rich and detailed source of explanatory data regarding perceived pregnancy risk of 15 women of AMA. The sample was recruited from a variety of settings in Winnipeg, Canada. In-depth interviews were conducted with nulliparous women aged 35 years or older, in their third trimester, and with singleton pregnancies. Interviews were recorded and transcribed verbatim, and content analysis was used to identify themes and categories. Results Four main themes emerged: definition of pregnancy risk, factors influencing risk perception, risk alleviation strategies, and risk communication with health professionals. Conclusions Several factors may influence women's perception of pregnancy risk including medical risk, psychological elements, characteristics of the risk, stage of pregnancy, and health care provider's opinion. Understanding these influential factors may help health professionals who care for pregnant women of AMA to gain insight into their perspectives on pregnancy risk and improve the effectiveness of risk communication strategies with this group.